El Estado como protector y destructor de la naturaleza en Chiapas, México - Trench, Tim (El Colegio de México, 2025)
This article explores two facets of re-cent environmental history of the state of Chiapas, to inquire about the processes of state formation in this historically marginalized state. Through two case studies —the establishment and operation of the Grijalva River Commission (GRC) and the evolution of conservation policy in the state— we contrast the State’s role as a destructive entity and at the same time protector of nature. Through archival material and secondary sources, this contribution explores how the State creates new contexts related to the management of the natural environment that open up new fronts of negotiation with the population, create new environmental identities and allow the authorization of its political agency.